Penguatan Pemberdayaan Kelompok Tani melalui Smart Nethouse dan Peningkatan Nilai Tambah Produk Hortikultura - Juliansyah, Akbar; Mulada, Diman Ade; Putrayadi, Wirawan; Rahman, Arief; Jarir, Jarir (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2025)
This Community Service Program (PKM) was implemented in the Taruna Tani Lombok Organik Farmer Group located in East Lombok Regency, West Nusa Tenggara Province. The main problems faced by partners include dependence on inefficient manual watering, poor control of the chili growing environment, and high risk of post-harvest losses due to traditional drying methods that depend on the weather. In addition, chili waste has not been optimally utilized as a value-added product. To address these issues, this PKM activity implemented solutions in the form of the construction and assistance in the application of Smart Nethouse based on automatic watering and Dome Solar Dryer based on solar energy. The implementation methods included socialization, technical training, operational assistance, and descriptive evaluation of changes in cultivation and post-harvest practices. The results of the activity show an increase in irrigation efficiency, farmers' understanding of microclimate management, acceleration of the chili drying process, and changes in farmers' attitudes towards the utilization of chili waste as an opportunity for derivative products. This program contributes to increasing the technical capacity of farmers and strengthening sustainable agricultural practices based on appropriate technology.